Ramsar Wetlands of International Importance–Improving Conservation Outcomes - Kingsford, R. T.; Bino, G.; Finlayson, C. M.; Falster, D.; Fitzsimons, J.A.; Gawlik, D. E.; Murray, N. J.; Grillas, P.; Gardner, R. C.; Regan, T. J.; Roux, D. J.; Thomas, R. F. (Frontiers in Environmental Science, 2021)
The Ramsar Convention, signed in 1971, was one of the first international conservation agreements, promoting global wise use of wetlands. It has three primary objectives: national designation and management of wetlands of international importance; general wise use of wetlands; and international cooperation. We examined lessons learnt for improving wetland conservation after Ramsar’s nearly five decades of operation. The number of wetlands in the Ramsar Site Network has grown over time (2,391 Ramsar Sites, 2.5 million km2, as at 9/6/20) but unevenly around the world, with decreasing rate of growth in recent decades. Ramsar Sites are concentrated in countries with a high GDP and human pressure (e.g. western Europe) but, in contrast, Ramsar sites with the largest wetland extent are in central-west Africa and South America. We identified three key challenges for improving effectiveness of the Ramsar Site Network: increasing wetland area; improved representation (functional, geographical and biological) and effective management and reporting. Increasing area in the Ramsar network could benefit from targets, implemented at national scales. Knowledge of representativeness is inadequate, requiring analyses of functional ecotypes, geographical and biological representativeness. Finally, most countries have inadequate management planning and reporting on the Ecological Character of their Ramsar Sites, requiring more focused attention on a vision and objectives, with regular reporting of key indicators to guide management. There are increasing opportunities to rigorously track ecological character, utilizing new tools and available indicators (e.g. remote sensing). It is critical that the world protect its wetlands, with an effective Ramsar Convention at the core.